A computed river flow-based turbine controller on a programmable logic controller for run-off river hydroelectric systems - Jidin R.; Othman A.B. (MDPI, 2023)
Computer circuits; Hydroelectric power; Ladders; Lakes; Mass transfer; Potential energy; Programmable logic controllers; Programmed control systems; Rivers; Stream flow; Turbines; Water levels; Hydroelectric; Hydropower; Ladder logic; Renewable energies; River flow; Turbine controllers; Controllers